Operational Risk Management Strategy Formulation of Curup Gangsa Lampung - Kesuma, Wahyu Puja; Sugiarto, Sugiarto; Kiswantoro, Amin (MSJ : Majority Science Journal, 2026)
Tourism activities in open natural environments inherently contain uncertainty that may evolve into operational risks when management control and supporting infrastructure are inadequate. Curup Gangsa Lampung, as a nature-based tourism destination, faces increasing visitor flow without a structured operational risk management system. This study aims to identify operational risk events, map risk levels using a Risk Evaluation Matrix, and formulate relevant mitigation strategies. The research employed a quantitative descriptive approach involving 260 respondents selected using purposive sampling. Data were analyzed using Importance Performance Analysis (IPA), Risk Evaluation Matrix, and Fishbone Diagram to identify priority risks and root causes. The findings reveal that operational risks originate from both natural and human-related factors, with visitor accidents classified as the most critical risk due to high frequency and impact. Several indicators fall into the “Concentrate Here” quadrant in IPA analysis, particularly signage, toilet conditions, infrastructure maintenance, and WiFi availability. The Fishbone analysis confirms that deficiencies in infrastructure and information accessibility are dominant causal factors. The study concludes that preventive improvements in infrastructure quality and information systems are essential to reduce operational risk exposure and enhance destination sustainability.